Defining cardiac fibrosis complexity and regulation towards therapeutic development - Bethany Claridge; Auriane Drack; Alexander R. Pinto; David W. Greening (Wiley, 2023)
Abstract Cardiac fibrosis is insidious, accelerating cardiovascular diseases, heart failure, and death. With a notable lack of effective therapies, advances in both understanding and targeted treatment of fibrosis are urgently needed. Remodelling of the extracellular matrix alters the biomechanical and biochemical cardiac structure and function, disrupting cell‐matrix interactions and exacerbating pathogenesis to ultimately impair cardiac function. Attempts at clinical fibrotic reduction have been fruitless, constrained by an understanding which severely underestimates its dynamic complexity and regulation. Integration of single‐cell sequencing and quantitative proteomics has provided new insights into cardiac fibrosis, including reparative or maladaptive processes, spatiotemporal changes and fibroblast heterogeneity. Further studies have revealed microenvironmental and intercellular signalling mechanisms (including soluble mediators and extracellular vesicles), and intracellular regulators including post‐translational/epigenetic modifications, RNA binding proteins, and non‐coding RNAs. This understanding of novel disease processes and molecular targets has supported the development of innovative therapeutic strategies. Indeed, targeted modulation of cellular heterogeneity, microenvironmental signalling, and intracellular regulation offer promising pre‐clinical therapeutic leads. Clinical development will require further advances in our mechanistic understanding of cardiac fibrosis and dissection of the molecular basis for fibrotic remodelling. This review provides an overview of the complexities of cardiac fibrosis, emerging regulatory mechanisms and therapeutic strategies, and highlights knowledge gaps and opportunities for further investigation towards therapeutic/clinical translation.